VD_FINDINFO Jug / 2015 / 329 vom 13. März 2015 - VD Tribunal cantonal (2015)
JUGE UNIQUE, PARTIE CIVILE, REJET DE LA DEMANDE, OPPORTUNITÉ, CONFRONTATION À UN ACTE D'ORDRE SEXUEL, PRÉSOMPTION D'INNOCENCE, TORT MORAL | 49 CO, 198 al. 2 CP, 52 CP, 10 CPP (CH), 126 CPP (CH), 398 al. 2 CPP (CH), 406 al. 1 let. c CPP (CH), 429 CPP (CH)